The role of regulatory T cells and follicular T helper cells in HBV infection - Lin, Nengqi; Yin, Wei; Miller, Heather; Byazrova, Maria G.; Herrada, Andrés A.; Benlagha, Kamel; Lee, Pamela; Guan, Fei; Lei, Jiahui; Gong, Quan; Yan, Youqing; Filatov, Alexander; et al. (Frontiers in Immunology, 2023)
Hepatitis B has become one of the major global health threats, especially in developing countries and regions. Hepatitis B virus infection greatly increases the risk for liver diseases such as cirrhosis and cancer. However, treatment for hepatitis B is limited when considering the huge base of infected people. The immune response against hepatitis B is mediated mainly by CD8+ T cells, which are key to fighting invading viruses, while regulatory T cells prevent overreaction of the immune response process. Additionally, follicular T helper cells play a key role in B-cell activation, proliferation, differentiation, and formation of germinal centers. The pathogenic process of hepatitis B virus is generally the result of a disorder or dysfunction of the immune system. Therefore, we present in this review the critical functions and related biological processes of regulatory T cells and follicular T helper cells during HBV infection.